Branding Denpasar Smart City Guna Meningkatkan Kunjungan Wisatawan - I Wayan Widana; Gede Sri Darma (Universitas Pendidikan Nasional, 2018)
ABSTRACTThis study concerning about the branding of smart city was conducted in Denpasar. The aim of present study was to: (1) describe the branding of Denpasar Smart City as an effort to increase the tourists’ visit, (2) identity challenges and obstacles to conduct the branding of Denpasar Smart City, and (3) describe the role of stakeholders to support the branding of Denpasar Smart City. This paper uses qualitative technique and collecting data was conducted through observation, interview and document study. Data analysis was carried out through data reduction, data display and conclusion and verification. The result suggest that it is required systematically, strategically and directionally branding study and branding framework of Denpasar Smart City involving various stakeholders. Some elements that need to be consider are how to build brand identity, brand positioning and brand image of Denpasar Smart City. It is required to strengthen promotion and campaign of Denpasar Smart City branding through three step of communication including primary communication, secondary communication and tertiary communication and also maximize the support of information and communication technology (ICT) and mobile application to share information with citizens and tourism and increase management of tourism destination. It was identified ten challenges and obstacles causing the branding of Denpasar Smart City was not optimal. Those need to be solved soon. The role of stakeholders are essential to support, promote and campaign the branding of Denpasar Smart City. Those stakeholders are the government, the academicians, the businessmen in tourism industry, the developers of smart city technology and application, communities or citizens, press and tourists.